Risk prediction in patients with COVID-19 based on haemodynamic assessment of left and right ventricular function. (28th August 2021) - Taieb, Philippe; Szekely, Yishay; Lupu, Lior; Ghantous, Eihab; Borohovitz, Ariel; Sadon, Sapir; Lichter, Yael; Ben-Gal, Yanai; Banai, Ariel; Hochstadt, Aviram; Merdler, Ilan; Sapir, Orly; et al.
Abstract: Aims: Cardiovascular involvement is common in COVID-19. We sought to describe the haemodynamic profiles of hospitalized COVID-19 patients and determine their association with mortality. Methods and results: Consecutive hospitalized patients diagnosed with COVID-19 infection underwent clinical evaluation using the Modified Early Warning Score (MEWS) and a full non-invasive echocardiographic haemodynamic evaluation, irrespective of clinical indication, as part of a prospective predefined protocol. Patients were stratified based on filling pressure and output into four groups. Multivariable Cox-Hazard analyses determined the association between haemodynamic parameters with mortality. Among 531 consecutive patients, 44% of patients had normal left ventricular (LV) and right ventricular (RV) haemodynamic status. In contrast to LV haemodynamic parameters, RV parameters worsened with higher MEWS stage. While RV parameters did not have incremental risk prediction value above MEWS, LV stroke volume index, E / e ′ ratio, and LV stroke work index were all independent predictors of outcome, particularly in severe disease. Patients with LV or RV with high filling pressure and low output had the worse outcome, and patients with normal haemodynamics had the best ( P < 0.0001). Conclusion: In hospitalized patients with COVID-19, almost half have normal left and right haemodynamics at presentation. RV but not LV haemodynamics are related to easily obtainable clinical parameters. LV but not RV haemodynamics are independent predictors of mortality, mostly in patients with severe disease.